2016
DOI: 10.1001/jama.2015.17844
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Use of Oral Fluconazole During Pregnancy and Risk of Spontaneous Abortion and Stillbirth

Abstract: In this nationwide cohort study in Denmark, use of oral fluconazole in pregnancy was associated with a statistically significant increased risk of spontaneous abortion compared with risk among unexposed women and women with topical azole exposure in pregnancy. Until more data on the association are available, cautious prescribing of fluconazole in pregnancy may be advisable. Although the risk of stillbirth was not significantly increased, this outcome should be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 35 publications
0
81
0
1
Order By: Relevance
“…However, some miscarriages may not be registered because of unawareness of pregnancy or missing hospital referral. Our study relied on hospital diagnoses and we restricted miscarriages to gestational weeks 7‐21 . It is likely that awareness of pregnancy is greater in women with surgery during early pregnancy than in women without surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some miscarriages may not be registered because of unawareness of pregnancy or missing hospital referral. Our study relied on hospital diagnoses and we restricted miscarriages to gestational weeks 7‐21 . It is likely that awareness of pregnancy is greater in women with surgery during early pregnancy than in women without surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated GA in days as GA(weeks)*7 + GA(days). Miscarriages before week 7 of gestation are poorly registered and were therefore not included . Live births at all GAs were registered in the DMBR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of these birth defects suggests that the teratogenic effect may occur early in the first trimester and has been confirmed by at least one animal study . Several studies support the risk of low‐dose fluconazole during pregnancy, especially when used for short durations . One recent cohort study identified an association between oral fluconazole during pregnancy and the risk of spontaneous abortion .…”
Section: Systemic Azole Antifungalsmentioning
confidence: 99%
“…44,45 One recent cohort study identified an association between oral fluconazole during pregnancy and the risk of spontaneous abortion. 45 Women who were exposed to either low-dose (150-300 mg) or high-dose (350-5600 mg) fluconazole during 7 through 22 weeks' gestation were matched to unexposed pregnancies. Fluconazole-exposed women had a significantly increased risk of spontaneous abortion compared with unexposed women (147 of 3315 and 563 of 13,246 women, respectively; hazard ratio [HR] 1.48, 95% CI 1.23-1.77).…”
Section: Fluconazolementioning
confidence: 99%